Drug Utilization Evaluation of Agents Administered for Prevention and Treatment of Cancer-Related Infections - Mohammad Mohammadzadeh; Ebrahim Farashi; Amir Reza Hesam; Seyed Hadi Chavoshi; Saba Ghaffary (Research Center for Rational Use of Drugs (RCRUD), 2021)
Backgrounds: Due to the critical role of antibiotics and increasing trend of resistance in developing countries, comprehensive methods of antibiotic use is necessary to limit the threat of resistant microorganisms. In this study we compare antibiotics consumption by Defined Daily Dose (DDD) per 100 bed-days in Shahid Ghazi hospitals during three months in Tabriz, Iran.Methods: This is a retrospective study, which enrolled patients with malignancy who admitted to Shahid Ghazi hospital from January till March 2016. From all, 58 patients diagnosed with malignancy and received antibiotics for prophylaxis and/or treatment. For the purpose of Drug Utilization Evaluation (DUE) all antibiotics, antifungals and antiviruses consumption for any reason (prophylaxis, empiric therapy, targeted therapy) were recorded. Data on administered medications such as indication, duration, and dose were compared according to the guidelines of the NCCN 2.2016. The accuracy of antibiotics consumption was assessing by NCCN (2.2016) guideline. Anatomical Therapeutic Chemical (ATC) code J01 was explained as defined daily doses per 100 bed-days (DDD/100) according to the ATC/DDD classification. The amount of consumption was assessed with DDD per 100 bed-days in three months. Results: from 56 patients, 46 of them had hematologic malignancy and 10 of them had solid tumors. The indication of antibiotics and antifungal prophylaxis were wrong in 19.6% of indications. The prophylaxis dosage of antibiotics, antifungal, antiviral and PCP were wrong in 8.8%, 41.7%, 80% and 50%, respectively. The prophylaxis duration of antibiotics, antifungal, antiviral and PCP were wrong in 69.4%, 61.2%, 80% and 100% respectively. The dose adjustment of antibiotics with GFR and renal status of patients, in 8 of 9 patients (88.88%) who received meropenem, and in 9 of 23 patients (39.13%) who received imipenem, were not applicable according standard guidelines. The total consumption of systemic antibiotics in Ghazi Hospital during 3 months was 5091From all patients 75% of them received antibiotics according to the ATC/DDD classification System. Conclusion: Specific strategies should be employed in infection control development and engage rational antibiotic utilization in order to reduce future resistant strains and increase anti-microbial efficacy.